Hubungan Pengetahuan dengan Perilaku Pencegahan Penularan Covid-19 Pada Ibu Hamil - Fitria Nurwulansari; Solihah (Institut Kesehatan dan Teknologi Al Insyirah, 2022)
Non-natural disasters caused by the Corona Virus or Covid-19 have spread and have an impact on maternal and child health problems. Covid-19 virus infection in pregnant women as a vulnerable group worsen the conditions of their pregnancy. Thus, an understanding of Covid-19 and its prevention is needed which will increase the awareness of pregnant women to take preventive measures against Covid-19. The purpose of this study was to analyze the relationship between knowledge and Covid-19 prevention behavior in pregnant women in the Independent Practice of Midwife